Anatomical studies of the secretory structures: glandular trichomes and ducts, in Grindelia pulchella Dunal (Astereae, Asteraceae) - Bartoli, Adriana (2011)
The ultrastructure of the glandular trichomes and secretory ducts of Grindelia pulchella was studied. Plastids, mitochondria and endoplasmic reticulum are involved in the secretory process of both, trichomes and ducts. A special tissue with “transfer cells” is associated with the duct epithelial cells. The secretion is produced in the transfer cells and then is transferred to the duct epithelial cells where it accumulates in the vacuoles. The occurrence of cavities within the cell walls of the trichome cells and duct epithelial cells is described. The secretion is accumulated between the cell wall and the cuticle of these cells. When the cuticle is broken the secretion is released. We conclude that granulocrine secretion operates in this species.